N-cadherin expression is a potential survival mechanism of gefitinib-resistant lung cancer cells - Yamauchi, Mai (e-Century Publishing Corporation, 2011)
Non-small cell lung cancer (NSCLC) is a major subtype of lung cancer and is the most common and fatal cancer worldwide. Specific tyrosine kinase inhibitors for epidermal growth factor receptor (EGFR), such as gefitinib, have been effective in some NSCLC patients and are being used in the clinical setting as pioneer molecularly targeted cancer drugs. However, many patients have not responded to these drugs, and have acquired resistance after long-term treatment. To identify other potential NSCLC molecular targets, we used DNA microarrays to examine gene expression profiles of gefitinib-resistant PC9/ZD cells that are derived from gefitinib-sensitive PC9 cells and harbor a threonine to methionine mutation at codon 790 (T790M) in EGFR, a known mechanism of acquired resistance to gefitinib. We found that N-cadherin expression was significantly upregulated in PC9/ZD cells compared with PC9 cells. Inhibition of N-cadherin expression by siRNA or treatment with antibodies against N-cadherin induced apoptosis of PC9/ZD cells in association with reduced phosphorylation of Akt and Bad, a proapoptotic protein. Moreover, inhibition of Akt expression by siRNA or treatment with an inhibitor for phosphatidylinositol (PI)-3 kinase reduced survival of PC9/ZD cells. In addition, we found several N-cadherin-expressing lung cancer cells that showed inherent resistance to gefitinib treatment and reduced survival owing to siRNA-induced inhibition of N-cadherin expression. Thus, it appears that N-cadherin maintains the survival of the gefitinib-resistant lung cancer cells via the PI-3 kinase/Akt survival pathway. From these results, we propose that N-cadherin signaling contributes, at least in part, to the survival mechanisms of gefitinib-resistant NSCLC cells and that N-cadherin is a potential molecular target in the treatment of NSCLC.